The effectiveness of teaching compassion focused therapy to parents on reducing aggression, behavioral problems and anxiety of children - Dinari, Parisa; Omidbakhtiari, Nikoo; Pouya, Matin; Mirzaei , Zahra; Heydari , Zahra; Farhadi, Aboozar (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of the present study was to determine the effectiveness of therapy training focused on compassion for parents on reducing aggression, behavioral problems and anxiety of children. Method: The present research was of applied and semi-experimental designs of pre-test-post-test type with control group. The statistical population of this research included all parents and children aged 8 to 10 who referred to the psychology clinic of Isfahan city in the second six months of 1401. The sample of this study includes 30 people who refer to counseling centers who were selected using available sampling method and were randomly placed in two experimental treatment groups focused on compassion for parents and a waiting list group. Data were obtained using aggression, behavioral problems, and anxiety questionnaires. The data were analyzed using the Mancova method and analysis of variance with repeated measurements, and the above statistical analyzes were performed using SPSS-26 software. Results: The results showed that the treatment focused on compassion for parents was effective in reducing aggression, behavioral problems and anxiety of children (P=0.05). Conclusion: Therefore, it can be concluded that the treatment focused on compassion for parents can be an effective intervention method to improve the reduction of aggression, behavioral problems and anxiety of children.